Подождите немного. Документ загружается.
ψ
3
= D (x
4
,x
5
,F(x
7
)) − u ,
u = D
0
⎛
⎜
⎜
⎝
x
5
x
0
5
−
T
1
x
5
x
0
5
m
β
1
x
5
x
0
5
−
N
N
0
+˜α
2
th
x
5
x
0
5
−
N
N
0
+
T
2
β
1
2
x
6
x
0
6
2
−1
⎞
⎟
⎟
⎠
.
ψ
3
=0
¨
ψ
3
(t)+˜α
3
˙
ψ
3
(t)+˜α
4
ψ
3
=0
u
3
u
3
= x
8
−
T
k
∂F
∂x
7
∂
2
F
∂x
2
7
(k x
8
)
2
+˜α
3
∂F
∂x
7
k x
8
+˜α
4
F (x
7
)
1 −
u
D
.
x
7
x
8
x
40
x
40
= f(N ).
D (x
4
,x
5
,F(x
7
)) − D (x
5
)=0;
∆H ·D
(x
5
) − N =0,
x
7
x
7
= x
0
7
f(N )
f(N )=
x
0
4
η
2ε −1
⎛
⎝
ε
0
ε +
ε
2
0
(1−ε )
2
−(2ε −1)
B
0
(x
0
5
/x
0
4
)
F (x
0
7
)
2
⎞
⎠
.
β
11
=1 β
12
=1 β
21
=1 β
22
=40 α
1
=0, 033
α
2
=0, 032 α
3
=0, 5 ˜α
2
=4 β
1
=2 ˜α
3
=4 ˜α
4
=3
x
0
6
= 314, 14 x
0
7
=0, 9
N
0
N
0
N
0
N
0
f ≈
0, 2 ÷ 1, 5
f>1, 5
•
•
•
•
•
•
cos ϕ
∆U
U = K
∆U
∆U + K
1U
d∆U
dt
+
i
K
∆
i
∆
i
+ K
i
d∆
i
dt
+ K
i
d
2
∆
i
dt
2
,
K
∆U
K
1U
K
∆
i
K
i
∆
i
D
p p = jω
D(jω)=K
2
D
2
(jω)+K
1
D
1
(jω)+D
0
(jω),
K
2
K
1
D
0
(jω)
K
2
P
1
(ω)+K
1
Q
1
(ω)+R
1
(ω)=0,
K
2
P
2
(ω)+K
1
Q
2
(ω)+R
2
(ω)=0,
P
1
Q
1
R
1
P
2
Q
2
R
2
D
2
(jω) D
1
(jω)
D
0
(jω)
K
2
K
1
ω 0 ±∞ D
K
1
=
∆
1
∆
,K
2
=
∆
2
∆
,
∆ ∆
1
∆
2
K
2
,K
1
D
u(t)
dV/dt < 0
u(t)
i
qi
=0
H
∞
K(p)
W
1
(p)
W
2
(p)
W
3
(p)
|W
1
(p)| |W
−1
3
(p)|
K(p)
W
i
(p),i = 1, 3
•
•
•
•